Diagnostic Accuracy of Lactate Dehydrogenase and Serum Creatine Kinase to Detect Prenatal Hypoxia in Term Neonates - Sabahat Fatima; Khadija Kiran; Anas Khalil; Jazib Andleeb; Farah Naz Tahir; Zahid Mahmood (Pakistan Journal of Medicine and Dentistry)
Background: Prenatal hypoxia is a condition where the fetus experiences insufficient oxygen levels and it can lead to morbidity and mortality. This study aimed to evaluate the diagnostic efficacy of the serum CK-MB fraction and LDH for the diagnosis of prenatal hypoxia.